Religion som fenomen og historie - til fornyelse og reinterpretasjon - Breivik, Nils Olav (Religionsvidenskabeligt Tidsskrift, 1986)
The classical phenomenology of religion has been severely criticized in the current methodological debate in religions studies. Among historians of religion there is, in spite of the deficiencies of earlier conceptions, a clear recognition of the necessity of a phenomenological approach. This essay seeks to present some recent attempts at reinterpretation and renewal of the phenomenology of religion. Among scholars discussed are Å. Hultkranz, J. Waardenburg, K. Rudolph, A. Rupp and R. Flasche. T here main tendencies may be pointed out in their studies: a) an attempt to overcome the conflict between history and phenomenology by regarding both as complementary approaches within a more integrated study of religion, b) A more conscious focus on religious man (the believer) to avoid the predetermined concept of religion. C) Renunciation of a worldwide phenomenology of religion in favour of a more regional one in order to secure the empirical basis for its conclusion.